Comparison of the Effect of Subcutaneous Administration of Anise Essential Oil and Oral Administration of Anise Aqueous Extract in BALB/c Mice Contaminated with Listeriosis - Amin Hashempour; Mohammad Hosein Sadeghi Zali; Saber Yousefi (Islamic Azad University, 2016)
Introduction: Studies have shown antibacterial activity of anise and on the other hand, Listeria monocytogenes, one Gram-positive pathogen is responsible for listeriosis. Thus, this study aimed to investigate the effect of subcutaneous administration of anise essential oil and oral administration of its aqueous extract and also comparison of their effects in BALB/c mice infected with listeriosis. Methods: Two units, by using insulin syringe, of Listeria monocytogenes prepared in 0.5 McFarland standard was intraperitoneally administrated to mice and agglutination test was done to ensure before anise administration. BALB/c mice (n=50) infected with listeriosis received anise aqueous extract (AAE) (5 g/100 g drink water) and 1-unit anise essential oil (AEO) by using insulin syringe was subcutaneously administrated to other mice (n=50) for 1 week. Other mice (n=24) were considered as control. Results: Results showed that AAE and AEO could improve mice contaminated with listeriosis, although mice treated with AAE were efficiently cured than those who received AEO (37 vs. 12). Conclusion: On the basis of the results, it can be recommended that the use of AAE for treatment of listeriosis is tenable.